CSR PROGRAM PT PERTAMINA BASED ON COMMUNITY EMPOWERMENT IN PEAT ECOTOURISM DEVELOPMENT - Nurjanah Nurjanah; Samsir Samsir (Sosiohumaniora, 2021)
Environmental problems that require serious handling are the problem of land and forest fires, especially on peatlands which cause losses, especially economic and environmental aspects. Peatlands are a natural resource that has the potential to be utilized for the welfare of the community. Utilization of peatlands is not only for agriculture, plantations and residential land, but can be used as peat ecotourism. The large number of peatlands that were initially not utilized, and most of them became unproductive idle lands, can be managed properly and are able to contribute samsirto improving the welfare of the surrounding communities through the company’s CSR program. This paper aims to analyze the management of the CSR program in the development of peat ecotourism in Bukit Batu DistrictPakning River.Researchers collected field data through interviews, observation and documentation. The results showed that the company’s CSR program is directed at developing various community empowerment programs, aiming for the community to have the power, strength or ability in physical and material aspects, as well as economic aspects.Utilization of post-fire peatlands with community empowerment in the process of developing peatland ecotourism through the Peat Typical Tree Planting program on burned land, the development of the Environmental-Based School Curriculum program and the Peat Arboretum Development program. The management of the CSR program is carried out through the planning, implementation and evaluation stages. The management of the CSR program is analyzed throughCommunity Based Tourism (CBT) Model which is a tourism development planning strategy.